Three-dimensional radiative effects in Arctic boundary layer clouds above ice edges - Schäfer, Michael; Bierwirth, Eike; Ehrlich, André; Jäkel, Evi; Wendisch, Manfred (Universität Leipzig, 2015)
Based on airborne spectral imaging observations, three-dimensional (3-D) radiative effects between Arctic boundary layer clouds and highly variable Arctic surfaces have been identified and quantified. A method is presented to discriminate sea ice and open water in cloudy conditions based on airborne upward radiance measurements in the visible spectral range. This separation simultaneously reveals that the transition of radiance between open water and sea ice is not instantaneous in cloudy conditions but horizontally smoothed. In general, clouds reduce the nadir radiance above bright surfaces in the vicinity of open water, while the nadir radiance above open sea is enhanced compared to situations with clouds located above sea ice surfaces. With the help of the observations and 3-D radiative transfer simulations, this effect was quantified. This affected distance deltaL was found to depend on both cloud and sea ice properties. For a low level cloud at 0-200 m altitude, as observed during the Arctic field campaign Vertical Distribution of Ice in Arctic Clouds (VERDI) in 2012, an increase of the cloud optical thickness from tau = 1 to tau = 10 leads to a decrease of deltaL from 600 to 250 m. An increase in cloud base altitude or cloud geometrical thickness results in an increase of deltaL. Furthermore, the impact of these 3-D-radiative effects on a retrieval of cloud optical properties was investigated. The enhanced brightness of a dark pixel next to an ice edge results in uncertainties of up to 90 % in retrievals of tau and up to 30 % in retrievals of the effective radius reff. With the help of detlaL quantified here, an estimate of the distance to the ice edge is given where the retrieval uncertainties due to 3D-effects are negligible. Mit Hilfe flugzeuggetragener abbildender spektraler Beobachtungen wurden 3-D Strahlungseffekte zwischen arktischen Grenzschichtwolken sowie der hochvariablen arktischen Bodenoberfläche identifiziert und quantifiziert. Eine Methode zur Differenzierung von Meereis und offener ...